Regulation of VanB-type vancomycin resistance gene expression by the VanS(B)-VanR (B) two-component regulatory system in Enterococcus faecalis V583. - Evers, S (1996)
Acquired VanA- and VanB-type glycopeptide resistance in enterococci is due to synthesis of modified peptidoglycan precursors terminating in D-lactate. As opposed to VanA-type strains which are resistant to both vancomycin and teicoplanin, VanB-type strains remain teicoplanin susceptible. We have determined the sequence of a 7,160-bp DNA fragment associated with VanB-type resistance in Enterococcus faecalis V583 that contains seven open reading frames. The distal part encoded the VanH (B), VanB, and VanX (B) proteins that are highly similar to the putative VanH, VanA, and VanX proteins responsible for VanA-type resistance. Upstream from the structural genes for these proteins were the vanY(B) gene encoding a D,D-carboxypeptidase and an open reading frame vanW with an unknown function. The proximal part of the gene cluster coded for the apparent VanS(B)-VanR (B) two-component regulatory system. VanR (B) was related to response regulators of the OmpR subclass, and VanS (B) was related to membrane-associated histidine protein kinases. Analysis of transcriptional fusions with a reporter gene and promoter mapping indicated that the VanR B-VanS B two-component regulatory system activates a promoter located immediately downstream from the vanS B gene. Vancomycin, but not teicoplanin, was an inducer, which explains teicoplanin susceptibility of VanB-type enterococci.